Information technologies in education: opportunities and negative consequences - Ihor Hevko (Kazimierz Wielki University, 2019)
The article discusses the impact of information education on the development of society. The article discusses the main problems and prospects of education informatization. In the information society, information technology occupies a special place. The use of information technology in the educational process significantly increases its effectiveness. Determined that the informatization of education is characterized by the use of computer-oriented teaching systems at different stages of training in higher and secondary schools, teaching the use of information technologies, which are, in turn, the procedural component of the computer-oriented educational systems. However, there are a number of problems complicating the process of informatization of education.